2017
DOI: 10.1136/bjophthalmol-2017-310716
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and cataract surgical coverage in Narayani Zone, Nepal: a rapid assessment of avoidable blindness (RAAB) study

Abstract: The prevalence of blindness in people over the age of 50 years has decreased from 6.9% in 2006 to 1.2%, a level in keeping with the national average; however, significant gender inequity persists. CSC has improved but continues to favour men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“… 7 In all three places, about 50%–60% of blindness and SVI was due to cataract. The prevalence of blindness and visual impairment in Kandze prefecture also resembled findings from RAAB studies in Jiangxi Province and Chaonan Region in China 8 9 and in Nepal 10 but lower than the Hainan Province in China. 11 …”
Section: Discussionsupporting
confidence: 69%
“… 7 In all three places, about 50%–60% of blindness and SVI was due to cataract. The prevalence of blindness and visual impairment in Kandze prefecture also resembled findings from RAAB studies in Jiangxi Province and Chaonan Region in China 8 9 and in Nepal 10 but lower than the Hainan Province in China. 11 …”
Section: Discussionsupporting
confidence: 69%
“…A 2016 population-based survey in the study area estimated a 3.7% prevalence of severe visual impairment or blindness among individuals ≥50 years of age, with the most common causes being cataract (76.2%), refractive error (6.9%), corneal opacity (3.0%), glaucoma (2.5%), AMD (2.5%), DR (1.5%) and other posterior segment disease (4.0%). 14…”
Section: Study Settingmentioning
confidence: 99%
“…The prevalence of visual impairment also varies across different age groups [11]. The Rapid Assessment of Avoidable Blindness (RAAB) survey conducted during 2008 to 2010 found that the prevalence of VI was 13.2% in the Bagmati and Janakpur zones of Nepal in those aged 50 years and above [12,13]. This study indicated the high magnitude of visual problems in Nepal.…”
Section: Introductionmentioning
confidence: 96%